Responses of six tomato (Lycopersicon esculentum Mill.) genotypes to salinity stress at low altitudes of Bengkulu, Indonesia - Suharjo, Usman KJ; Nababan, Sartika Y; Masdar, Masdar; Pamekas, Tunjung; Mukhtasar, Mukhtasar (Akta Agrosia, 2018)
Salinity stress causing water deficit, nutrient deficiency, and ion imbalance for the crops has been reported to reduced crop growth, crop yield, and fruit quality in tomatoes. The main objective of this research were to determine the LC-50 of salinity, to evalute the response of six tomato genotypes to LC-50, and to study the effect of genotype and salinity stress on crop growth, crop yield, and fruit quality of tomatoes. The LC-50 of salinity was determinated by growing tomato seedlings at different level of saline solutions (0, 400, 500, 6000, 7000, 9000, 10000, 11000, and 12000 ppm of NaCl) and used the LC-50 of salinity to evaluate the salinity tolerance of six tomato genotypes. The results showed that the LC-50 of saline solution was 9000 ppm NaCl and genotype Empat G was found to be the most tolerant to salinity stress